2015
DOI: 10.7566/jpsj.84.085003
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Thermal Transport of Layered Bismuth-Sulfide EuBiS2F at Temperatures between 300 and 623 K

Abstract: We demonstrate the electrical and thermal transport of the layered bismuth-based sulfide EuBiS2F from 300 to 623 K. Although significant hybridization between Eu 4f and Bi 6p electrons was reported previously, the carrier transport of the compound is similar to that of F-doped LaBiS2O, at least above 300 K. The lattice thermal conductivity is lower than that of isostructural SrBiS2F, which is attributed to the heavier atomic mass of Eu ions than that of Sr ions.Searching for novel thermoelectric materials is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…The power factor increased with increasing concentration of Se, i.e., Se substitution led to an enhanced electrical conductivity, without suppression of the Seebeck coefficient. Hall measurements indicated that the low electrical resistivity resulted from increases in the carrier mobility, and the decrease in carrier concentration led to large absolute values of the Seebeck coefficient of the system.LaOBiCh2 (Ch: S, Se) and related Bi-Ch layered compounds have attracted significant attention as new thermoelectric materials [1][2][3][4]. The crystal structure of LaOBiCh2 consists of alternating stacks of an electrically conducting BiCh2 bilayer and an insulating La2O2 layer.…”
mentioning
confidence: 99%
“…The power factor increased with increasing concentration of Se, i.e., Se substitution led to an enhanced electrical conductivity, without suppression of the Seebeck coefficient. Hall measurements indicated that the low electrical resistivity resulted from increases in the carrier mobility, and the decrease in carrier concentration led to large absolute values of the Seebeck coefficient of the system.LaOBiCh2 (Ch: S, Se) and related Bi-Ch layered compounds have attracted significant attention as new thermoelectric materials [1][2][3][4]. The crystal structure of LaOBiCh2 consists of alternating stacks of an electrically conducting BiCh2 bilayer and an insulating La2O2 layer.…”
mentioning
confidence: 99%
“…This material shows metallic conductivity and shows a superconducting transition at 0.4 K [32]. Goto et al measured thermoelectric properties of EuFBiS2 at high temperatures [53]. Figures 6(a,b) show the temperature dependences of  and S for EuFBiS2.…”
Section: -2 Eufbis2mentioning
confidence: 99%
“…The highest ZT was 0.36 at ∼650 K, and the ZT is expected to increase at higher temperatures. Studies on the thermoelectric properties of BiCh 2 ‐related compounds have just started in several groups with various compounds . The LaOM 2 S 3 (M = Bi, Pb) structure (Figure e) with four‐layer‐type M 4 S 6 conduction layers is also a candidate for new thermoelectric materials, because of the M 4 Ch 6 ‐type conduction layer similar to that of CsBi 4 Te 6 , which is a high‐performance thermoelectric material and a superconductor .…”
Section: Bich2‐based Compounds As Thermoelectric Materials or Other Fmentioning
confidence: 99%